Perbandingan Kemampuan Menahan Beban Aksial Kolom Pendek Berlubang Dengan Variasi Jarak Sengkang - Muhamad Iqbal Dafa Pratama; Mohamad Galuh Khomari Khomari; I Ketut Hendra Wiryasuta; M. Shofi'ul Amin; Mirza Ghulam Rifqi (Journal of Applied Civil Engineering and Infrastructure Technology, 2026)
This study investigates the effect of stirrup spacing variation on the axial load capacity of short reinforced concrete columns with openings. The research focuses on square cross-section short columns measuring 12 cm × 12 cm × 45 cm, incorporating a pipe opening that reduces the cross-sectional area by 5.58%. The objective is to determine whether varying the stirrup spacing can enhance the axial compressive strength of perforated columns, which typically experience strength reduction due to the decreased cross-sectional area. The study was conducted experimentally in a laboratory using 20 MPa concrete, with longitudinal reinforcement of ø10 mm and stirrups of ø6 mm. Two types of columns were tested: solid columns (with 19 cm stirrup spacing) and perforated columns (with 8 cm stirrup spacing). Test results indicate that reducing stirrup spacing in perforated columns was not sufficiently effective to equal or surpass the axial strength of solid columns. The solid columns had an average axial compressive strength of 296.71 kN, while the perforated columns with 8 cm stirrup spacing showed a slightly lower strength of 288.92 kN, representing a decrease of 2.62%.